Variação ecogeográfica e funcional do crânio de Tayassuidae (Mammalia: Artiodactyla) - Hendges, Carla Deonisia (2018)
Understanding the determining mechanisms and functional roles of phenotypic variation have been a central topic of ecogeography and evolution. Peccaries are excellent models for testing ecogeographical and functional hypotheses given the extensive geographic distributions ranging across both Northern and Southern hemispheres of two of the three living species as well the evolution of skull features that presuppose high biomechanical performance. In this thesis, we used geometric morphometrics procedures and univariate and multivariate analyses of variance to describe the geographical variation in skull shape and size of Pecari tajacu and Tayassu pecari and to test the influence of environmental, allometric and spatial factors. We also investigated if skull shape of the three living peccaries reflect their biomechanical attributes. In the first chapter, we obtained the skull shape for 294 specimens of both P. tajacu and T. pecari from 134 different localities in South America. Using Partial Least Squares and variation partitioning analysis we quantified the relationship between the skull shape and the environmental, spatial and allometric factors. Our results revealed patterns of geographical variation in skull shape of both species, but shape is more conservative in T. pecari. The environment explained most of this variation, while a weak allometric and spatial autocorrelation effect was found only in P. tajacu. In the second chapter, we tested the geographical variation in skull size of 426 specimens of both species from 174 different localities south of the equator and 83 in the north. We regressed the skull size against latitude. Effects of seasonal temperature, precipitation, and human influence including spatial autocorrelation structures were tested through Generalized Least Squares. Differences in size between sympatric and allopatric areas were explored with ANOVA models. We found a latitudinal pattern in skull size of peccaries, one inverse to Bergmann Rule. Size was positively associated with precipitation, offering support to resource availability as a major mechanism behind increases in lower latitudes, especially for T. pecari. Human influence affects negatively the size of peccaries in Southern hemisphere. The largely non-overlapping body-size distributions of the two species suggest that size differences may be necessary for sympatric overlap of these two peccaries. In chapter 3, combining geometric morphometrics and biomechanical analyses we obtained the skull shape and centroid size from 213 specimens of the three living peccary species and estimated bite force, bite stress at molars, bending and shear stress on the mandibular corpus, and condylar stress. We found that P. tajacu and T. pecari share craniomandibular shape traits (shorter and deeper mandibular corpora and wider muscle insertion areas) enabling them to apply stronger forces and resist stress and fractures from higher biomechanical demands than P. wagneri. In a broader sense, our results highlight the role of the environmental variation driving clinal variation in skull shape and size, especially the resource availability. The results also corroborate the hypothesis that shape closely reflects the biomechanical performance of species.